Early Versus Late Tracheostomy in Outcome of Patients Admitted in Neurosurgical Intensive Care Unit - Rai, Shiwani; Sharma, Prasansa; Makajoo, Sofiya; Karmacharya, Balgopal; Yogi, Nikunja (Eastern Green Neurosurgery, 2020)
Background: Tracheostomy is a commonly performed procedure in neurosurgical Intensive Care Units (ICU) performed to secure airway, aid in pulmonary toileting, and minimize ventilator-associated pneumonia (VAP) in cases requiring prolonged mechanical ventilation. Although early tracheostomy has been advocated rampantly in recent days, its benefit over late tracheostomy and the timing itself has been very controversial. In this study, we tried to study the effect of timing of tracheostomy in the outcome of patients in our ICU. Materials and methods: This is a retrospective study carried out over a period of one and a half years in a tertiary care center in western Nepal. Early tracheostomy was defined as those done within 4 days of endotracheal intubation and late were those done thereafter. Outcomes were studied in terms of length of ICU stay, hospital stay, mechanical ventilation, duration of tracheostomy in situ, VAP and mortality and complication over 90 days. Statistical analysis was done using SPSS 20.0. Results: There were 67 cases included in the study, out of which 27(40.3%) underwent early and 40 (59.7%) underwent late tracheostomy. The Mean duration of ICU stay, tracheostomy in situ duration, mechanical ventilation duration, and VAP were the parameters showing a significant difference between the two groups. There were 13 (19.4%) cases having complications in our series of which 6 (9%) of cases were from the early tracheostomy group and 7 (10.4%) of the cases were from the late tracheostomy group (p=0.63). Conclusion: Early tracheostomy is beneficial in a neurosurgical patient in terms of a decrease in ICU stay, duration of mechanical ventilation, duration of tracheostomy in situ, and VAP.